Meetings with the teaching work: dimensions of the professional development in the Pedagogical Residence Program/UFPB - Andrade, Barthyra Cabral Vieira de (Revista Letras Raras, 2023)
This discussion is based on my experience as an advisor professor of the Pedagogical Residence Program of Universidade Federal da Paraíba, inserted in the group of Letters- Spanish and English languages. This context of teachers education allows us to see the process of building one´s teacher identity and the professional development of the Letters students, pre-service teachers, through their relationship with the collectives and in the discovery of their singularities. My analytical reflection is the result of reading reflective reports written along the years 2018 and 2019 and seeks to highlight some dimensions of this process. Based on the basic principles that make up the framework of Socio-discursive Interactionism such as the definitions of significant action and the capacity to act (BRONCKART, 1999/2006) and, in particular, the understanding that language has a fundamental role in human development, I describe the path covered by the residents of the group, making evident their development as teachers and emphasize, based on the notion of discursive worlds or action coordinates (HABERMAS, 1987) the social and subjective aspects that underlie this development. Reading the residents´ texts resulted in the finding that the collective dimension, through encounters and mismatches, strengthens their work and ends up making them develop a particular and more mature relation with teaching.